SURFACE QUALITY CONTROL AFTER GRINDING - Okyu'lova Nigora Inobidin's daughter (Bright Mind Publishing, 2025)
In order to increase production efficiency and improve product quality, great importance is attached to measurement techniques, primarily the development and implementation of automated measurement systems that increase the efficiency of existing controls, reduce the number of controllers, and actively receive information about product quality. Objective: To identify technological deficiencies and defects in mandrels and recommend advanced techniques and technologies for their improvement, as well as to increase labor efficiency by introducing them into production.
Keywords: Prototyping, presses, smoothing, Lathes for drilling, tapping, countersinking, and boring.